Incidence and management of adverse events associated with panobinostat in the treatment of relapsed/refractory multiple myeloma. (April 2019) - Moore, Donald C; Arnall, Justin R; Harvey, R Donald
Multiple myeloma is a plasma cell neoplasm that has seen impressive improvements in outcomes in recent years with combination therapies, such as proteasome inhibitors and immunomodulatory drugs. Histone deacetylase inhibition is an additional unique mechanism of action with established biological relevance in multiple myeloma. Panobinostat is the first histone deacetylase inhibitor indicated for the treatment of relapsed/refractory multiple myeloma in patients who have received at least two prior regimens, including bortezomib and an immunomodulatory agent. While the addition of panobinostat to bortezomib and dexamethasone has demonstrated response and progression-free survival benefits, the incidence and severity of adverse events associated with it can create a challenge for clinicians and patients. Specifically, diarrhea, myelosuppression, an increased risk for infectious complications, cardiotoxicity, and nausea/vomiting may be seen with use. The frequency and grade of adverse event occurrence may differ between doses and schedule of panobinostat as well as with different companion therapies and routes. Herein we discuss the incidence, severity, and practical management of adverse events associated with panobinostat in the treatment of relapsed/refractory multiple myeloma.